Training Small Scale Industry Extension Workers in Information Use - Sharma, S. V. S.; Dutta, S.; Haravu, L. J. (Journal of Information and Knowledge, 1978)
Describes the small industry scene in India and outlines the role of small industry extension workers in industrial development. Stresses the value of information in enabling extension workers to perform their role effectively. States that two important factors that will determine the effective use of information are -(i) accessibility to information, and (ii) awareness of information sources, information generators and skills in the exploitation of sources and other information systems. Highlights the need for information networking as a means to increase information accessibility to extension workers and training of such workers to make better use of information. Describes what SIET has done in making extension workers aware of information and its use, in general, and SIET’s training programme on ’Information Storage and Retrieval Systems’ in particular, the clientele agencies. Presents possible areas of Indo-US cooperation in for which are drawn mainly from industrial development this work.